Innovation in retail: impact on creating a positive experience when buying fashion products - Cristinel Vasiliu; Mihai Ovidiu Cercel (Amfiteatru Economic Journal, 2015)
Innovation in fashion retail is critical in order to ensure competitive advantage in a constantly evolving market, in terms of consumer expectations. The modern customer is mobile, permanently connected to the Internet, well-informed about international trends, mindful of the quality of products, but more price sensitive and less loyal to a brand. The shopping experience provided by retailers is a crucial factor in purchase decision, encompassing all these variables in a complex concept of exogenous variable. As retailers' efforts to provide excellence in shopping experience are focused on operating costs and thus on the profit margins, it is important to consider and identify which are the most relevant variables that form the perception of excellence for Romanian customers, so that retailers can innovate according to their expectations. The purpose of this article was to highlight the role of innovation in creating a positive experience for consumers buying clothes, shoes and accessories. The approach was based on the conduct of exploratory research. The research - represented by five original objectives and as many different working scenarios - resulted in the identification of thematic outlined exploratory opinions, exploiting a first investigation of its kind in Romania, less Pearson coefficients used in the analysis of ordinal variables or hierarchical, but quickly assessed using SPSS, version 21. As a pioneering research emphasis was on identifying potential associations and quantified correlations and less on rigorous delimitation of exogenous or endogenous quality in general, leaving room for future studies, sharper and with a higher degree of representation. Thus, we could highlight some useful aspects of the investigated retailers, by the dominant character of interested customers' opinions according to their volunteer responses. Consumers are accustomed to using the Internet to obtain information; they rarely express opinions on social sites about the purchased goods, and are willing to receive information about special offers of the stores on personal mobile devices since the entry into the stores. Customers would also welcome separate exposure areas in selling space, where they can find products in promotional campaigns. Therewith, we could outline a primary profile of the ideal salesperson on fashion products, less rigorous but relatively consistent.
Keywords: L81; O33; 330; retail; shopping experience; fashion products; salesperson; brand; innovation in retail